Direct Z-scheme CdFe2O4/g-C3N4 hybrid photocatalysts for highly efficient ceftiofur sodium photodegradation. (1st November 2020) - Fang, Miao-Miao; Shao, Jun-Xia; Huang, Xiang-Gang; Wang, Jin-Yi; Chen, Wei
Abstract: A direct Z-scheme CdFe2 O4 /g-C3 N4 hybrid systems with different weight ratios of CdFe2 O4 nanoparticles were successfully designed and constructed for ceftiofur sodium photodegradation. The as-obtained CdFe2 O4 /g-C3 N4 hybrid samples composed of CdFe2 O4 nanoparticles and g-C3 N4 nanosheets were systematically characterized by different techniques including X-ray diffraction, scanning electron microscope, transmission electron microscope, Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy, UV–vis DRS, chemical oxygen demand, inductively coupled plasma mass spectrometer, photochemical test and electron spin resonance spectrometer technique. The optimal photocatalytic activity for ceftiofur sodium photodegradation was achieved by modulating the weight ration between CdFe2 O4 nanoparticles and g-C3 N4 nanosheets. The result from photocatalytic tests indicate that CdFe2 O4 /g-C3 N4 -2 hybrid sample exhibit highly efficient photocatalytic activity towards ceftiofur sodium removal in comparison with pristine CdFe2 O4 nanoparticles and pure g-C3 N4 nanosheets. Meanwhile the excellent photocatalytic stability of CdFe2 O4 /g-C3 N4 -2 hybrid sample was also verified during recycling runs towards photocatalytic ceftiofur sodium degradation. The significant enhancement of photocatalytic activity was attributed to the Z-scheme charge separation and transfer based on the construction of tight heterogeneous interface and well-matched band potentials. We expect this research to provide a new insight into the design and preparation of direct Z-scheme hybrid photocatalysts for environmental remediation.